Assessment: A Suggested Strategy for Learning Chemical Equilibrium - Andres Bernal-Ballen; Yolanda Ladino-Ospina (Education Sciences, 2019)
Chemical equilibrium is listed as one of the most complicated concepts to learn, and the origin of this phenomenon is attributed to misconceptions, teaching-related problems, and the use of inappropriate didactic approaches. At the same time, assessment is a crucial fragment of educational activities although its relevance as a learning strategy is underestimated. For that reason, we designed and applied unique assessment approaches related to chemical equilibrium to 33 high school students at Colegio Mayor de San Bartolome (Bogotá, Colombia). The results suggested that assessment instruments focused on the identified misconceptions might reduce the impact (of the misconceptions), and students were able to build concepts related to chemical equilibrium whilst they were being assessed. Problems associated with forward and reverse reactions, differences between initial and equilibrium concentrations, and the indiscriminate use of Le Chatelier’s principle were approached by students and significant improvement was achieved through the assessment. Changes associated with assessment perceptions were accomplished and the proposed strategy suggests that it is plausible to learn during the assessment moment.